Functional Abdominal Pain Disorders in Children - Muzal Kadim (The Indonesian Society for Digestive Endoscopy, 2021)
Diagnostic criteria for functional abdominal pain has developed in the last decade, from the Rome III criteria to the Rome IV criteria. The major change was in the phrase